Effects of stagnant zone on the effectiveness factor in a trickle bed. (2nd February 2022) - Tang, Yanling; Luo, Gang; Zhong, Juhua; Chen, Kaixuan; Xu, Chenqian; Cheng, Zhenmin
Graphical abstract: Highlights: The influence of stagnant zone on the effectiveness factor is investigated. A high-speed video camera is used to verify the validity of simulation. Mass transfer limitation caused by liquid pocket is more serious than liquid pendulum. Simulation of effectiveness factor is approximated by a three-particle string. Abstract: Industrial trickle-bed reactors are normally operated under complete wetting conditions, almost 20–30% of the particle external surface is covered by stagnant liquid. To investigate the influence of stagnant zone on the effectiveness factor, a multi-particle string model is studied by CFD simulation, with a high-speed video camera verifying the validity of simulation. It shows that stagnant liquid in liquid pendulum and liquid pocket would cause obvious external mass transfer limitation at high Thiele moduli, yet the effects of liquid pocket are more serious than liquid pendulum. The effects of liquid velocity, particle diameter, and particle number on effectiveness factor are evaluated. The effectiveness factor belonging to single particle due to absence of liquid pocket is higher than that of a multi-particle string, while the three-particle string model is similar to the four-particle approach, which indicates simulation of effectiveness factor in a trickle bed can be approximated by a three-particle string.